2006
DOI: 10.2172/915026
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of VHTR system modeling needs based on phenomena identification, ranking and sensitivity studies.

Abstract: A major debt of gratitude is owed to Dr. Won-Jae Lee of the Korea Atomic Energy Research Institute (KAERI) and his KAERI colleagues for the very productive collaboration on the companion I-NERI project. The insights, results and ideas conveyed through discussions, presentations, and documentation during the course of the companion I-NERI project "Screening of Gas-Cooled Reactor Thermal Hydraulic and Safety Analysis Tools and Experimental Database" has been very beneficial. We convey our thanks in this acknowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Example of successful PIRT applications in thermal-hydraulics, severe accidents, fuels, materials degradation, and nuclear analysis may be found in [34]. An extensive application of PIRT is reported in [33,35,36], for the determination of code applicability for the analysis of selected scenarios with uncertainty evaluations.…”
Section: Phenomena Identification and Ranking Tables (Pirt)mentioning
confidence: 99%
“…Example of successful PIRT applications in thermal-hydraulics, severe accidents, fuels, materials degradation, and nuclear analysis may be found in [34]. An extensive application of PIRT is reported in [33,35,36], for the determination of code applicability for the analysis of selected scenarios with uncertainty evaluations.…”
Section: Phenomena Identification and Ranking Tables (Pirt)mentioning
confidence: 99%
“…The literature indicates that the development of a PIRT-like (phenomena identification and ranking table) approach has a strong likelihood for identifying the key phenomena in the LP [Vilim, Pointer, and Wei, 2006;Lee et al, 2007;Olivier and Nowlen, 2008]. Indeed, various attempts have been made recently for the VHTR LP, and this research focuses on many of those that have been identified already [McEligot, D. M. et al, 2005;Vilim, Pointer, and Wei, 2006]. Based on the literature and a desire to include simplified to more complex fluid phenomena, a set of key fluid phenomena were selected for CFD simulations.…”
Section: Fuego Validation and Verification (Vandv)mentioning
confidence: 99%
“…Based on the literature and a desire to include simplified to more complex fluid phenomena, a set of key fluid phenomena were selected for CFD simulations. The cases that were selected for V&V are listed in Table VI, and are as follows The above seven phenomena are strongly related to flow distribution, as well as thermal mixing and stratification; and are issues that received a "high" ranking in a recent VHTR PIRT study that was conducted by Argonne National Laboratory [Vilim, Pointer, and Wei, 2006].…”
Section: Fuego Validation and Verification (Vandv)mentioning
confidence: 99%
“…High pressure, high temperature experiments were to be conducted to obtain data that would be used for validation of VHTR design and safety analysis codes. As shown in several Phenomena Identification and Ranking Tables (PIRT) for VHTRs (Vilim et al, 2006;Ball et al, 2007;Schultz et al, 2008) under normal operation, transient, and accident scenarios, the key phenomena leading to localized hot spots in the reactor core include degraded heat transfer in coolant channels, laminarization of flow, effects of bypass flow and nonuniform heat generation across the core. Some of these phenomena would be investigated using a unique high pressure, high temperature heat transfer facility to be set up at City College of New York.…”
Section: Introductionmentioning
confidence: 99%